Support for tourism: the roles of attitudes, subjective wellbeing, and emotional solidarity. Issue 2 (1st February 2023) - Munanura, Ian E.; Needham, Mark D.; Lindberg, Kreg; Kooistra, Chad; Ghahramani, Ladan
Abstract: Research models applying social exchange theory to examine factors predicting residents' support for tourism have been challenged for their inability to explain support fully. Recent studies drawing from other theories indicated factors that arguably play a role in the social exchange relationship between perceptions of tourism impacts and support. One factor of interest is the cognitive appraisal process eliciting emotional solidarity with tourists (ES), which arguably predicts support. According to cognitive appraisal theory (CAT), residents' emotional feelings toward tourists result from a mental evaluation of how tourism is perceived to impact one's wellbeing. Although tourism studies applying CAT are emerging, knowledge is limited about the cognitive appraisal process that elicits ES. This article examines the nature of a cognitive appraisal process eliciting ES. Data were obtained from a random sample of 1477 residents of Oregon, United States. Results from a structural equation model, show that perceived positive tourism impacts strongly predict ES. Additionally, perceived positive tourism impacts indirectly impact ES through the expected change of wellbeing. This study also reveals that perceived negative community tourism impacts have a negative relationship with ES. Moreover, ES strongly predicts support. The article closes with a discussion of research and management implications.